Air density dependence of the soft X-ray PTW 34013 ionization chamber. (February 2018) - Torres del Río, Julia; Forastero, Cristina; Tornero-López, Ana M.; López, Jesús J.; Guirado, Damián; Perez-Calatayud, José; Lallena, Antonio M.
Highlights: The dependence on air density of the PTW 34013 ionization chamber is analyzed. The standard pressure-temperature correction is enough for low energy X-ray beams. An additional dependence on air-density occurs for medium-high X-ray beams. Abstract: Purpose: We studied the dependence on air density of the response of the PTW 34013 ionization chamber, recently upgraded for dosimetry control of low energy X-ray beams. Methods: Measurements were performed by changing the pressure conditions inside a pressure chamber. The behavior of the measurements against the air density inside this chamber was analyzed. X-ray beams generated with 50, 70, 100, 150 and 200 kVp and the two electrometer polarities were considered. Results: For all beams studied, measurements corrected with the conventional temperature and pressure factor showed a residual dependence on the air density that was described with a linear function of the air density. For the 50 and 70 kVp beams, corrected measurements remained ∼ 1 % smaller than the value found at standard pressure/temperature conditions, for both electrometer polarities and for the air density range typical in clinical conditions. For air densities smaller than the standard one, measurements found for 100, 150 and 200 kVp beams were below or above the value found at standard pressure and temperature when the negative or positive electrometer polarities were used, respectively. The differences with the measurements at standard conditions were less than 1 % for the 100 kVp beam and below 4 % for the other two beams. Conclusions: The PTW 34013 ionization chamber showed a dependence on the air density that is not properly described with the usual temperature and pressure correction factor. This residual dependence is negligible for low energy beams, for which this chamber is recommended, but is more substantial for beams with energy above 80 kVp.